Insurance for the Uninsured: Exploring Drivers of Life Insurance Intent in Ghana’s Informal Economy - Akura-Asase , Edna Yawa; Abra Amenuku, Mary; Mohammed, Bashiru (International Journal of Scientific Research and Management (IJSRM), 2025)
This study investigates the factors influencing life insurance purchase intention among informal sector workers in Ghana, a demographic that remains largely uninsured despite being financially vulnerable. Drawing on the Theory of Planned Behavior and Theory of Reasoned Action, the research explores how consumer insurance literacy, price of life insurance, and consumer confidence in insurance affect purchase intention, with attitude toward life insurance serving as a mediating variable. Using a cross-sectional survey design and Partial Least Square Structural Equation Modeling (PLS-SEM) on data collected from 560 informal workers using a questionnaire, the findings reveal that insurance literacy and consumer confidence positively and significantly influence purchase intention, while the price of life insurance exerts a negative effect. Attitude toward life insurance was found to partially mediate the relationships between all three independent variables and purchase intention. These results highlight the psychological and informational drivers behind insurance uptake decisions in underinsured populations. The study contributes to the behavioral finance literature by contextualizing insurance behavior in an informal economy and offers practical implications for insurers and policymakers aiming to expand life insurance coverage among low- to middle-income earners in emerging markets.